PENGETATAN POLIGAMI DI INDONESIA PERSPEKTIF MAQASHID SYARIAH DAN HUKUM POSITIF - Aqil, Izan Syarifurrohman (UIN Palopo, 2023)
Polygamy is a solution to social problems given in Islam, how an adult male can marry more than one woman. of course it is not arbitrary for an adult man to do this, he must also know the laws and provisions that apply in Fiqh, and the State, especially in countries in Indonesia where there are constitutional laws as well as positive laws, through this research with the title: tightening polygamy in Indonesia; the perspective of Maqasid Sharia and positive law, is expected to be a solution for Muslims to the anxiety that occurs in Islamic society in Indonesia.